C‐Src‐dependent transactivation of EGFR mediates CORM‐2‐induced HO‐1 expression in human tracheal smooth muscle cells. Issue 10 (October 2015) - Yang, Chuen‐Mao; Lin, Chih‐Chung; Lee, I‐Ta; Hsu, Chih‐Kai; Tai, Yu‐Chen; Hsieh, Hsi‐Lung; Chi, Pei‐Ling; Hsiao, li‐Der
<x xml:space="preserve">Abstract</x> Carbon monoxide (CO), a reaction product of the cytoprotective heme oxygenase (HO)‐1, displays an anti‐inflammatory effect in various cellular injuries, but the precise mechanisms of HO‐1 expression remain unknown. We used the transition metal carbonyl compound carbon monoxide‐releasing molecule‐2 (CORM‐2) that acts as carbon monoxide donor. The effects of CORM‐2 on expression of HO‐1 in human tracheal smooth muscle cells (HTSMCs) were determined by Western blot, real‐time PCR, and promoter activity assay. In HTSMCs, CORM‐2 activated Nrf2 through the activation of a c‐Src/EGFR/PI3K/Akt‐dependent pathway, resulting in HO‐1 expression. We showed that CORM‐2‐induced HO‐1 protein and mRNA levels were inhibited by the inhibitor of c‐Src (PP1 or SU6656), EGFR (AG1478), PI3K (LY294002), Akt (SH‐5), JNK1/2 (SP600125), or p38 MAPK (SB202190) and transfection with siRNA of c‐Src, EGFR, Akt, p38, JNK2, or Nrf2 in HTSMCs. We also showed that CORM‐2 stimulated c‐Src, EGFR, Akt, p38 MAPK, and JNK1/2 phosphorylation. CORM‐2 also enhanced Nrf2 translocation from the cytosol to the nucleus and antioxidant response element (ARE) promoter activity. Moreover, CORM‐2 mediated p38 MAPK and JNK1/2 activation via a c‐Src/EGFR/PI3K/Akt pathway, which further enhanced Nrf2 activation and translocation. Finally, we observed that CORM‐2 induced in vivo binding of Nrf2 to the HO‐1 promoter. CORM‐2 activates the c‐Src/EGFR/PI3K/Akt/JNK1/2 and p38 MAPK pathways, which in turn trigger Nrf2 activation and ultimately induces HO‐1 expression in HTSMCs. Thus, the HO‐1/CO system might be potential therapeutics in airway diseases. J. Cell. Physiol. 230: 2351–2361, 2015. © 2015 Wiley Periodicals, Inc.